An estimation of sonic velocities in shale using clay and silt fractions from the elemental capture spectroscopy log - Pervukhina, M.; Golodoniuc, Pavel; Gurevich, Boris; Clennell, M.; Nadri, D.; Dewhurst, D.; Nordgard Bolas, H. (EAGE, 2012)
Anisotropic differential effective medium approach is used to simulate elastic properties of shales from elastic properties and volume fractions of clay and silt constituents. Anisotropic elastic coefficients of the wet clay pack are assumed to be independent of mineralogy and to be linearly dependent on clay packing density (CPD), a fraction of clay in an individual wet clay pack. Simulated compressional and shear velocities normal to the bedding plane and are shown to be in a good agreement with measured sonic velocities. Further, elastic coefficients of shales, and, calculated from the log sonic velocities, calibrated porosity and clay fraction obtained from the mineralogy tool are used to invert for elastic constants of clays, C33 and C44. The obtained elastic coefficients of clays show lower scatter than the original elastic coefficients of shales. The noticeable increase of the clay elastic coefficients with the depth increase is shown to result from the positive trend of the CPD with depth. Being interpolated to the same CPD = 0.8, elastic coefficients of clays show no depth dependency. Our findings show that the CPD and silt fraction are the key parameters that can be used for successful modelling of elastic properties of shales.